Struktur Modal Terhadap Return Saham Perusahaan Sektor Industri Di Indonesia - Dinarossi Utami; Frecilia Nanda Melvani; Riri Hanifa (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This research examines the influence of capital structure on stock returns of industrial sector companies in Indonesia. Capital structure in this study is measured by long term debt to capital, total debt to capitalization, short term debt to total assets, and debt to equity ratio, while the dependent variable is the stock return of companies in the Industrial Sector. This research data is panel data from Industrial Sector companies listed on the Indonesia Stock Exchange for the period 2015 to 2022. The sampling technique was non-probability and sample selection was based on purposive sampling to obtain 38 companies. The research data analysis method uses multiple regression analysis. The research results show that a company's capital structure can influence stock returns in the industrial sector. Capital structure refers to the composition of the sources of funds used by a company, such as share capital and debt. Each industrial sector has a preference for a different capital structure. Stable industries with predictable revenues may tend to have lower capital structures. Meanwhile, companies in fastgrowing sectors may be more inclined to use debt to fund growth.